Structural and optical properties of TiO2:NiO nanoparticles thin films prepare by chemical spray pyrolysis - Wasan A. Al-Taa'y; Bushra A. Hasan (Iraqi Journal of Physics, 2021)
The properties of structural and optical of pure and doped nano titanium dioxide (TiO2) films, prepared using chemical spray pyrolysis (CPS) technique, with different nanosize nickel oxide (NiO) concentrations in the range (3-9)wt% have been studied. X-Ray diffraction (XRD) technique where using to analysis the structure properties of the prepared thin films. The results revealed that the structure properties of TiO2 have polycrystalline structure with anatase phase. The parameters, energy gap, extinction coefficient, refractive index, real and imaginary parts were studied using absorbance and transmittance measurements from a computerized ultraviolet visible spectrophotometer (Shimadzu UV-1601 PC) in the wavelengths range (300-800)nm. Optical properties of TiO2 affected by the adding of NiO impurity where the transmittance increased as NiO concentration increased but with more adding the transmittance returned to decrease again. It was found the extinction coefficient, refractive index, real and imaginary parts values decreased with increasing doping percentage up to 7% and then increases occur one more again at 9%. Energy gap values increased after doping with NiO where the values lies in the range was 3.31 to 3.51 eV .